Somatostatinoma syndrome: a challenging differential diagnosis among pancreatic tumors - Vianna, Paula Martinez; Ferreira, Cristiane Rúbia; Campos, Fernando Peixoto Ferraz de (Autopsy and Case Reports, 2013)
Among the neuroendocrine neoplasia, the pancreatic somatostatin-producing tumors are very rare. Usually functional, these tumors produce the somatostatinoma syndrome, which encompasses diabetes mellitus, diarrhea/steatorrhoea, and cholelithiasis. Other symptoms may include dyspepsia, weight loss, anemia, and hypochlorhydria. All theses symptoms are explained by the inhibitory actions of the somatostatin released by tumoral cells originated from pancreatic delta cells or endocrine cells of the digestive tract. The diagnosis is easy to overlook since these symptoms are commonly observed in other more common syndromes. Besides the clinical features, diagnosis is based on serum determination of somatostatin, and imaging exams, such as ultrasound, computer tomography and positron emission tomography. Pathologic examination is characterized by the positivity of immunohistochemical reaction for synaptophysin, chromogranin, and somatostatin. These tumors can be classified according to tumor size, mitotic index, neural or vascular invasion, and distant metastases. The authors describe the case of a 61-year-old female patient who sought medical care because of a 6-month history of watery diarrhea, weight loss, and depression. She was diagnosed with diabetes mellitus 3 years ago. Imaging examination revealed a tumoral mass of 4 cm in its longest axis in the topography of the head of the pancreas and calculous cholecistopathy. The patient’s clinical status was unfavorable for a surgical approach. She died after 20 days of hospitalization. The definitive diagnosis was achieved with the autopsy findings, which disclosed a pancreatic somatostatinoma.